DEVELOPING MSME, ENTREPRENEURSHIP, AND MARKETING BUSINESS RESULTS OF SIWANG REBON PRODUCTS IN SINGAJAYA INDRAMAYU VILLAGE - Agus Yudianto; Meddy Nurpratama (Universitas YPPI Rembang, 2022)
Entrepreneurship in this activity is defined as the ability to create something new and different from others, so the team decided to disseminate information about the importance of entrepreneurship in the post-covid-19 pandemic. Furthermore, this product manufacturing program is an activity to create new products so the team decides to carry out product manufacturing practices.In the product marketing program, this activity is directed to market products to social media so that it is announced to do product marketing through social media by residents. Increasing public awareness of the Entrepreneurship program which is quite encouraging.The entrepreneurship program can be said to be successful because of the 30% of residents who have not dared to carry out entrepreneurial activities after entrepreneurship socialization, it can increase to 70%. This is based on observations by the service team. The increase in public awareness of the product manufacturing program can be said to be successful because of the 50% of residents who have not yet made the product, it has increased to 70% after the team has practiced product making. This is based on observations by the service team.Increasing public awareness of the product marketing program can be said to be successful because from 30% of residents who do not understand online marketing, it has increased to 80% after the team has practiced marketing through social media. This is based on program observations by the service team..